Classroom teaching skills. - Moore, Kenneth D. (New York : London : Tokyo : McGraw-Hill, 1995)
Prospective teachers need to develop a repertoire of skills that have proven to be effective and to enhance learning. Practicing professionals need to sharpen their skills and improve on their level of mastery. Classroom Teaching Skills was written to satisfy these needs. This text, a compact skills reference, is organized around a comprehensive model of teaching that includes planning, implementation, and evaluation components. The skills addressed are common to instruction at all grade levels and in all subject areas. Taken as a whole, the skills presented might be thought of as a minimum repertoire of skills that all teachers need to acquire. The text is written in a concise, easy-to-read fashion. The book has been carefully designed to maximize instructional flexibility and to model established principles of instruction. Each chapter begins with specific learning objectives that help focus the reader's attention. The reader's understanding of key concepts is then checked through a series of self-tests that appear at the end of subsections within the chapters. End-of-chapter answer keys provide immediate feedback on how well the chapter objectives are met. Practicing teachers and prospective teachers will find that this highly organized, densely packed text will fulfill the need for a compact skills reference. Most of the skills addressed in this text can be found on state and national lists of basic teaching competencies.
Includes bibliographical references and index.
Keywords: Teaching -- Handbooks, manuals, etc; Classroom management